Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.brat.2008.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Emotional states preceding and following acts of non-suicidal self-injury in bulimia nervosa patients

Abstract: Bulimia nervosa and non-suicidal self-injury (NSSI) co-occur at high rates, and both have been conceptualized as maladaptive emotion regulation strategies. Treatments focusing on emotion regulation have been designed for both problem behaviors, yet, there exists very little research examining the temporal emotional states surrounding acts of NSSI. Using ecological momentary assessment (EMA) methodology, the current study examined the temporal association between positive and negative emotional states prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
160
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 193 publications
(177 citation statements)
references
References 49 publications
(55 reference statements)
13
160
1
3
Order By: Relevance
“…countries (Garner et al 1985;Yellowlees, 1985;Mitchell et al 1986;Gleaves & Eberenz, 1993;Pryor et al 1996;Tobin & Griffing, 1996;Wiederman & Pryor, 1996a, b;Favaro & Santonastaso, 1997, 1998Nagata et al 2000a;Steiger et al 2001;Anderson et al 2002;Dohm et al 2002;Paul et al 2002;Stein et al 2004;Ruuska et al 2005;Corstorphine et al 2007;Ahren-Moonga et al 2008;Bulik et al 2008;Fichter et al 2008;Muehlenkamp et al 2009;Liang & Meg Tseng, 2011;Peebles et al 2011;Iannaccone et al 2013;Vansteelandt et al 2013;Bueno et al 2014). The 29th publication (Solano et al 2005) shared participants with the sample in Bueno et al (2014).…”
Section: Search Resultsmentioning
confidence: 99%
“…countries (Garner et al 1985;Yellowlees, 1985;Mitchell et al 1986;Gleaves & Eberenz, 1993;Pryor et al 1996;Tobin & Griffing, 1996;Wiederman & Pryor, 1996a, b;Favaro & Santonastaso, 1997, 1998Nagata et al 2000a;Steiger et al 2001;Anderson et al 2002;Dohm et al 2002;Paul et al 2002;Stein et al 2004;Ruuska et al 2005;Corstorphine et al 2007;Ahren-Moonga et al 2008;Bulik et al 2008;Fichter et al 2008;Muehlenkamp et al 2009;Liang & Meg Tseng, 2011;Peebles et al 2011;Iannaccone et al 2013;Vansteelandt et al 2013;Bueno et al 2014). The 29th publication (Solano et al 2005) shared participants with the sample in Bueno et al (2014).…”
Section: Search Resultsmentioning
confidence: 99%
“…Our results corroborate previous micro-longitudinal studies that have shown that weekly co-occurrence of NSSI and DE may be quite common. Even when study samples are recruited based on their engagement in one of these behaviors, secondary analyses show that roughly 15 to 40% of participants have engaged in other selfdamaging behaviors during the monitoring periods (Anestis et al, 2012;Muehlenkamp et al, 2009;Shingleton et al, 2013). In the current study, 25 of the 60 participants (42%) who were selected for their engagement in NSSI reported some DE behavior during the two-week diary period.…”
Section: Co-occurring Non-suicidal Self-injury and Disordered Eating 16mentioning
confidence: 99%
“…Bolger, Davis, and Rafaeli (2003) provide a review of the benefits of such programs, including timestamps for responses, flexibility in presentation of questions, and more efficient data entry and management. Recent studies have used electronic handheld devices to investigate physical symptoms (e.g., physical anxiety symptoms; Pfaltz, Michael, Grossman, Margraf, & Wilhelm, 2010;Smyth & Stone, 2003), behaviors such as alcohol consumption (Collins et al, 1998;Hufford, Shields, Shiffman, Paty, & Balabanis, 2002;Kashdan, Ferssizidis, Collins, & Muraven, 2010;Simons, Dvorak, Batien, & Wray, 2010;Swendsen et al, 2000), drug use (Buckner, Crosby, Silgado, Wonderlich, & Schmidt, 2012;Buckner et al, 2011), eating disorder symptoms (Engel et al, 2007;le Grange, Gorin, Dymek, & Stone, 2002;Muehlenkamp et al, 2009;Wegner et al, 2002), and psychological constructs such as affect (Juth, Smyth, & Santuzzi, 2008;Trull et al, 2008), mood disorders/depressive symptoms (aan het Rot, Hogenelst, & Schoevers, 2012;Vranceanu, Gallo, & Bogart, 2009;Wenze & Miller, 2010), self-esteem (Kernis, 2005), social anhedonia and social anxiety (Brown, Silvia, Myin-Germeys, & Kwapil, 2007;Buckner, Crosby, Wonderlich, & Schmidt, 2012), and anxiety symptoms in general (Gallagher, Schoemann, & Pressman, 2011). A recent review has highlighted the use of electronic EMA as a part of psychosocial and health behavior interventions (Heron & Smyth, 2010).…”
Section: Handheld Devicesmentioning
confidence: 99%